Defining Spirituality in Healthcare: A Systematic Review and Conceptual Framework - de Brito Sena, Marina Aline; Damiano, Rodolfo Furlan; Lucchetti, Giancarlo; Peres, Mario Fernando Prieto (Frontiers in Psychology, 2021)
Objective: To investigate the definitions of spirituality in the healthcare field, identifying its main dimensions and proposing a framework that operationalizes the understanding of this concept. Methods: This is a systematic review following the PRISMA guideline (PROSPERO: CRD42021262091), searching for spirituality definitions published in scientific journals. Searches were carried out in PubMed (all articles listed up to October 2020) and in the reference lists of the articles found in the database, followed by selection under specific eligibility criteria. Results: From a total of 493 articles, 166 were included in the final analysis, showing that there is a large body of scientific literature proposing and analyzing spirituality definitions. In these articles, 24 spirituality dimensions were found, most commonly related to the connectedness and meaning of life. Spirituality was presented as a human and individual aspect. These findings led us to construct a framework that represents spirituality as a quantifiable construct. Conclusions: Understanding spirituality is an important aspect for healthcare research and clinical practice. This proposed framework may help to better understand the complexity of this topic, where advances are desirable, given the relevance it has acquired for integral health care.